Quality Of Life Patients With CAD After Percutaneous Coronary Intervention At Cardiac Center Rsup Dr. Hasan Sadikin Bandung - Syifa Aulia; Aan Nuraeni; Hasniatisari Harun (Universitas Padjadjaran, 2020)
Quality of life of patients CAD after PCI needs to be seen as an evaluation of the interventions carried out, which need to be studied continuously by looking at health status, socioeconomic, and differences in the measurement tools used can be found differences from each item measured. This study aims to look at the quality of life of patients with CAD after PCI at the cardiac center of RSUP Dr. Hasan Sadikin Bandung. This study uses a quantitative descriptive method with a cross-sectional approach. The samples in this study were all patients CAD after PCI who were outpatient at RSHS Bandung. Samples were taken using purposive sampling technique and obtained 100 respondents. Data is collected using Macnew instruments by analyzing data using frequency distribution.The results showed that 95 respondents (95%) had a high quality of life. The quality of life results based on subvariables from highest to lowest are obtained as follows; emotional subvariable (94%) with a mean of 5.90, social subvariable (94%) with a mean of 5.84 and physical subvariable (93%) with a mean of 5.60.In conclusion, almost all respondents have a high quality of life which is reinforced by the results of high social and emotional aspects, but the physical aspects still need to be improved by providing adequate information regarding the patient's disease and the benefits of attending cardiac rehabilitation to improve the quality of life. In addition, physical, emotional and social management plays an important role in improving the quality of life of patients.Keywords: After Percutaneous Coronary Intervention, Coronary Heart Disease, Quality of Life